Unformatted text preview: g ( x , y ) = xy 2 + e xy + 3. Let f ( x , y , z ) = g ( x , y )-z-2. Then the level surface f ( x , y , z ) =-2 is g ( x , y )-z-2 =-2 which implies z = g ( x , y ). This shows that the desired function is, f ( x , y , z ) = g ( x , y )-z-2 = xy 2 + e xy-z + 1 or, alternatively, f ( x , y , z ) = z-g ( x , y )-2 = z-xy 2-e xy-5...
View Full Document
This note was uploaded on 04/04/2011 for the course MA 3160 taught by Professor Staff during the Spring '08 term at Michigan Technological University.
- Spring '08
- Multivariable Calculus